The study of the effectiveness of thrombolysis while an ischemic cerebrum infarction - Y. L. Zhuravkov; A. N. Grishkevitch; A. A. Koroliova; A. E. Shnip (Military Medicine, 2026)
The original results of the assessment of the effectiveness of thrombolysis by alteplaza while an ischemic cerebrum infarction at Minsk City Clinical Hospital Emergency Medical Care are resulted in the article.